Exigência de Metionina + Cistina para Frangos de Corte na Fase de Crescimento e Acabamento - Rodrigueiro, Ramalho José Barbosa; Albino, Luiz Fernando Teixeira; Rostagno, Horacio Santiago; Gomes, Paulo Cezar; Pozza, Paulo Cezar; Neme, Rafael [UNESP] (My University, 2000)
With the objective to determine the methionine+cystine requirements, 1440 and 1080 commercial Hubbard broilers were used, 50% of each sex at the growing and finishing phases, respectively. Six supplemental levels of DL-methionine (.0, .06, .12, .18, .24, and .30%) were added to methionine+cystine deficient basal diets. Body weight gain, feed intake, feed:gain ratio, carcass yield and composition, abdominal fat and plasma uric acid concentration were evaluated from 22-42 and 43-56 days of age. Based on the statistical analysis of the studied parameters during the growing phase (22 to 42 days of age), it is suggested to use .896 and .856% of total methionine+cystine for males and females, respectively. For the finishing phase (43 to 56 days of age), based in the statistic analysis and in the studied parameters, it is suggested to use .764% and .740% of total methionine+cystine for males and females, respectively.
Methionine+Cystine Requirement for Broilers at the Growing and Finishing Phases
Keywords: Broilers; Carcass yield; Composition carcass; Performance; Sulfur amino acids requirements